Women as Co Bearers of the Imago Dei - Gyantinus, Febrian Wahyu; Luma, Subaedah; Tuela, Anita I (Peneliti.net, 2025)
This study explores the theological implications of Imago Dei for gender equality in the Indonesian context, emphasizing the equal status of women as co-bearers of the divine image. Drawing on a qualitative method with a critical literature review approach, this research analyzes biblical texts, theological interpretations, and socio-cultural realities related to gender discrimination. The study revisits the Hebrew terms tselem and demuth (Genesis 1:26–27), underscoring that both men and women reflect God’s likeness through intellect, morality, and relational capacity. However, patriarchal interpretations—especially within Old Testament narratives—have historically marginalized women by framing them as subordinate to men. In the Indonesian cultural context, these theological biases are compounded by social and linguistic constructs that reinforce gender hierarchy. The findings reveal that feminist theological frameworks provide a constructive reinterpretation of women’s roles in Scripture, portraying figures like Deborah, Hannah, and Rahab as agents of faith and leadership. This study concludes that recognizing women as co-image bearers of God is essential for theological reform and gender justice, and it urges the church to dismantle patriarchal structures, promote inclusive leadership, and collaborate with broader human rights efforts in Indonesia.